2008
DOI: 10.1002/pmic.200700588
|View full text |Cite
|
Sign up to set email alerts
|

Subunit–subunit interactions in the human 26S proteasome

Abstract: Ubiquitin-dependent proteolysis is mediated by the proteasome. To understand the structure and function of the human 26S proteasome, we cloned complete ORFs of 32 human proteasome subunits and conducted a yeast two-hybrid analysis of their interactions with each other. We observed that there are 114 interacting-pairs in the human 26S proteasome. About 10% (11/114) of these interacting-pairs was confirmed by the GST-pull down analysis. Among these observed interacting subunits, 58% (66/114) are novel and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…4B) can fulfill these restraints. Thus, our cross-linking data derived from the fully assembled 26S pro- teasome comply with the published protein-protein interaction data, such as Rpt2 binding to α4 (35,36), as well as genetic data suggesting Rpt2-α3 interaction (37), but they do conflict with the interactions reported for the synthetic C-terminal Rpt peptides (e.g., Rpt5-α3 and Rpt5-α4) (33,34). This discrepancy might be explained by different binding specificities of the full-length proteins as compared to the short C-terminal peptides.…”
Section: Resultssupporting
confidence: 83%
“…4B) can fulfill these restraints. Thus, our cross-linking data derived from the fully assembled 26S pro- teasome comply with the published protein-protein interaction data, such as Rpt2 binding to α4 (35,36), as well as genetic data suggesting Rpt2-α3 interaction (37), but they do conflict with the interactions reported for the synthetic C-terminal Rpt peptides (e.g., Rpt5-α3 and Rpt5-α4) (33,34). This discrepancy might be explained by different binding specificities of the full-length proteins as compared to the short C-terminal peptides.…”
Section: Resultssupporting
confidence: 83%
“…Rpt3 and Rpt6 are nearest neighbors in the base complex, 11 and the Rpt3-Rpt6 association has been observed before. 23,[29][30][31][32][33] The following interactions have also been found: Rpn13 with Rpn2, 12,[34][35][36] Rpn2 with Rpn10, 37 Rpn11 with Rpn10, 38 Txnl1 with Rpn11, 13 and Txnl1 with Rpn2. 16 Isono et al found an intact lid complex in yeast cells.…”
Section: Discussionmentioning
confidence: 77%
“…To obtain a most accurate model, it will be important to remove erroneous protein-protein interaction data. For example, recent in vitro redesign of the CP-AAA-ATPase interface suggests that Rpt5 binds to the ␣ 3 /␣ 4 CP pocket (86), whereas the data underlying our CP-AAA-ATPase model suggest that Rpt2 binds to ␣ 4 (87,88), and genetic data indicate interaction of Rpt2 with ␣ 3 (89). Thus, taking into account the data from Yu et al (86), two conflicting models are possible where either Rpt2 or Rpt5 interact with the ␣ 3 /␣ 4 CP pocket.…”
Section: Integrative Structure Determination Of the Rpmentioning
confidence: 88%